Cost-Benefit Analysis of Leaning Against the Wind : Are Costs Larger Also with Less Effective Macroprudential Policy? - Svensson, Lars (IMF Working Papers; Working Paper ;, 2016)
'Leaning against the wind' (LAW) with a higher monetary policy interest rate may have benefits in terms of lower real debt growth and associated lower probability of a financial crisis but has costs in terms of higher unemployment and lower inflation, importantly including a higher cost of a crisis when the economy is weaker. For existing empirical estimates, costs exceed benefits by a substantial margin, even if monetary policy is nonneutral and permanently affects real debt. Somewhat surprisingly, less effective macroprudential policy and generally a credit boom, with resulting higher probability, severity, or duration of a crisis, increases costs of LAW more than benefits, thus further strengthening the strong case against LAW.